Midwifery Students’ Perspectives on Medical Daily Conversations in Ahmad Izzan’s English for Professionals - Astutie, Elma; Syamsara, Amaliya; Syahid, Abdul (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study explores midwifery students' perceptions of Ahmad Izzan's textbook, "English for Medical Professionals," in enhancing their medical English communication skills. Using a descriptive quantitative approach, the research employed a structured questionnaire comprising both open-ended and close-ended questions to gather in-depth insights. The survey focused on aspects such as the textbook's relevance, clarity, practicality, and its perceived effectiveness in clinical communication. Results indicate that students generally regard the textbook as beneficial, particularly in improving their comprehension and application of medical English in practical settings. However, the small sample size limits the generalizability of the findings. Expanding the study with a larger participant pool is suggested to provide more comprehensive insights into the textbook’s impact. These findings aim to inform curriculum design and teaching methods that better prepare midwifery students with the communication skills essential for their professional development.